PEMBUDIDAYAAN JAMUR KUPING PADA SEBELAS JENIS KAYU - Sihati Suprapti (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
he ear mushroom, Auricularia polytrica (Basidiomycetes: Auriculariaceae) was cultivated on logs of eleven wood species, i.e. hamerang (Ficus grossularoides Burn, f.), jeungjing (Albizia falcataria (L.) Fosb.), kaliandra (Calliandra calothyrsus Meissn.), kihuut (Vernonia arborea Ham.), kipiit (Maesa ramentacea Wall.), kiwates (Eurya acuminata AP. DC.), manii (Maesopsis eminii Engl.), sehang (Ficus padana Burn. f.), seuseureuhan (Piper aduncum L.), teureup (Artocarpus elastica Reinw.) dan tusam (Pinus merkusii Jung et de Vr.). The logs were kept slanted on an angle of ± 60° with bamboo supports in a mushroom house, at Gunung Bunder forest complex, Bogor. The mature mushroom were harvested daily after the growth of the fruiting body.The logs start producing fungus two months after inoculation. The average yield per log during the seven month observation was 412.15 g (sehang), 302.43 g (manii), 251.6 g (seuseureuhan), 243.6 g (kihuut). The lower yield was 28.85 g (kiwates), 12 g (jeungjing) and 8.85 (tusam).After seven month observation, the higher total yield was obtained from manii (83.18 kg), seuseureuhan (79.97 kg), sehang (76.91 kg), kihuut (69.09 kg) perm3 of log. The lower total yield per m3 of log was obtained from kaliandra (29.35 kg), teureup (22.75 kg), kiwates (11.98 kg), Jeungjing (4.45kg) and the lowest total yield was on tusam (1.87 kg).